Prediction of temporary epicardial pacing wire use in cardiac surgery. Issue 8 (15th July 2020) - Cote, Claudia L.; Baghaffar, Abdullah; Tremblay, Philippe; Herman, Christine R.
Abstract: Background: Placement of temporary epicardial pacing wires (TEPW) at the end of open heart surgery cases is routine but can be associated with complications. Identification of patients who are high risk for requiring pacing would be beneficial on guiding selective TEPW placement. The purpose of this study was to identify predictors of temporary pacing immediately post cardiac surgery. Methods: A retrospective analysis of patients undergoing cardiac surgery from 2005 to 2016 at the Maritime Heart Center was conducted. Analysis was performed of patients who require pacing on arrival to the cardiovascular intensive care unit (CVICU) compared with those who were not paced. Multivariable logistic regression was used to determine each variable's risk adjusted likelihood of pacing for the entire cohort. Subgroup analysis was performed in the isolated procedures. Results: A total of 11 752 patient underwent surgery from the year 2005 to 2016. Two thousand and fifty‐one (17.5%) required pacing on arrival to CVICU. Older age, female sex, preoperative renal failure, lower ejection fraction (EF), preoperative arrhythmia, preoperative use of calcium channel blockers, and longer cross‐clamp times were risk factors for pacing. In the isolated coronary artery bypass grafting and aortic valve replacement groups, findings were similar to the overall cohort. Only age, obesity, and chronic obstructive pulmonary disease were risk factors for pacing in the isolated mitral valve (MV) repair group and only preoperative arrhythmia in the isolated MV replacement group. Conclusion: We have identified risk factors for TEPW use following cardiac surgery and in isolated procedure subgroups. These risk factors may help guide selective TEPW placement.